Metodologi Tafsir Gender: Telaah Kritis Pemikiran Husein Muhammad: The Methodology of Gender Interpretation: A Critical Study of Husein Muhammad's Thought - Ash-Shufi, Cep Gilang Fikri (Journal of Islamic and Occidental Studies, 2024)
This article aims to explore and criticize the gender interpretation methodology used by Husein Muhammad, especially in interpreting Qur'anic verses related to women. For Husein, the Qur'an cannot be separated from the historical aspects of 7th century Arab society. This is evidenced by the fact that the Qur'an has reasons for the revelation of verses, as well as the periods of Makkah and Madinah. Therefore, the method of historical criticism based on hermeneutics must be applied in understanding the Qur'an. Husein applied this method and elaborated it into four other methods; maqāshid-based interpretation method, socio-historical aspect analysis method, language analysis method, and causality aspect study method. From there, an understanding of the verse is born in accordance with the concept of gender equality. The results of this study show that Hussein's hermeneutic cannot be applied to the Qur'an, because hermeneutics was born in the Western-Christian tradition motivated by their disappointment with the Bibles, while the Qur'an does not have such a history. Moreover, hermeneutics is based on doubt, whereas Qur'anic exegesis is based on faith. Hermeneutics views the Bible as an unholy text, while the Qur'an is kept sacred and authentic.